The Relationship Between Pancasila Student Profile Strengthening Project (P5) with Entrepreneurship Theme and Elementary Students’ Independent Attitude - Trio Bagus Darmawan; Ristiana Dyah Purwandari (UM Purwokerto Press, 2025)
This research aims to identify the relationship between student involvement in the Pancasila Student Profile Strengthening Project (P5) with Entrepreneurship theme and the independent attitude of elementary school students. The research used a quantitative approach with ex post facto method and involved 69 fifth and sixth grade students at Sidanegara 04 Elementary School, Central Cilacap, as the sample. The main instrument was a Likert scale questionnaire developed to measure two variables: the level of involvement in P5 projects and students' independent attitude. Data were analyzed using Pearson Product Moment correlation after validity, reliability, normality, and linearity tests. The results showed that there is a strong and significant positive relationship between student involvement in P5 projects with Entrepreneurship theme and independent attitude (r = 0.684; p < 0.01). Each stage of project implementation, from planning, production, marketing to evaluation, contributes to the formation of independent attitude dimensions such as decision-making ability, responsibility, self-confidence, perseverance, and independence in completing tasks. These findings indicate that the implementation of P5 projects can be an effective strategy in developing students' independent character through contextual, active, and meaningful learning experiences.